2007
DOI: 10.1016/j.cub.2007.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Dia-Interacting Protein Modulates Formin-Mediated Actin Assembly at the Cell Cortex

Abstract: These observations point to a pivotal role for DIP in the control of nonbranched and branched actin-filament assembly that is mediated by Diaphanous-related formins and activators of Arp2/3, respectively. The ability of DIP to trigger blebbing also suggests a role for mDia2 in the assembly of cortical actin necessary for maintaining plasma-membrane integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 39 publications
4
106
1
Order By: Relevance
“…The 'activated' mDia1 could then bind to its other partners, such as POPX2. A similar observation has been reported for mDia2 and DIP, whereby the binding of CDC42 to mDia2 relieves the auto-inhibition of mDia2 and allows its interaction with DIP (Eisenmann et al, 2007). Thus, the interaction of mDia1 with POPX2 might provide a mechanism for fine modulation of mDia1 activity.…”
Section: Discussionsupporting
confidence: 78%
“…The 'activated' mDia1 could then bind to its other partners, such as POPX2. A similar observation has been reported for mDia2 and DIP, whereby the binding of CDC42 to mDia2 relieves the auto-inhibition of mDia2 and allows its interaction with DIP (Eisenmann et al, 2007). Thus, the interaction of mDia1 with POPX2 might provide a mechanism for fine modulation of mDia1 activity.…”
Section: Discussionsupporting
confidence: 78%
“…Only few studies previously addressed the involvement of specific actin nucleators in PM blebbing. Using experimental systems in which PM blebbing was induced by genetic manipulation or protein overexpression, nucleators such as mDia1, mDia2, FHOD1, Arp2/3 that are also involved in the regulation of diverse additional cellular actin remodeling events were implicated in blebbing [12,[41][42][43]. In this present study, we conducted a comprehensive analysis of the involvement of endogenously expressed human actin nucleators in PM blebbing of adhering HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Much less is understood about the regulation of this F-actin network; nonetheless it is clear that RhoA and the ROCK kinases are critical for its maintenance. In addition, it has recently been shown that modulation of Dia2 [20] and PDK1 [97,98] activity can affect cortical actin. High levels of RhoA, RhoC or ROCK activity promote contraction of the cortical actin that is associated with membrane blebbing [99].…”
Section: Actin Organisation In Complex Environmentsmentioning
confidence: 99%
“…Like WAVE and WASP family proteins, FH proteins also switch between an auto-inhibited 'closed' conformation and an active 'open' conformation [6]. Interaction with numerous GTP-binding proteins, including Cdc42, RhoA, RhoB and Rif, and adaptor proteins such as DIP/WISH can stabilise the open conformation thereby promoting actin polymerization driven by the FH2 domain [18][19][20][21][22]. Structural studies indicate that FH2 domains function as dimers with one FH2 domain binding a monomer in the existing actin filament and the other FH2 domain recruiting a new G-actin monomer for polymerisation [23].…”
mentioning
confidence: 99%